Analysis of the Functioning Practice of the Insurance Market of the Republic of Uzbekistan (Eurasian Journal of Humanities and Social Sciences, 2023)
At the moment, the insurance market of Uzbekistan continues to develop and attract the attention of foreign investors. This article analyses the insurance market of the Republic of Uzbekistan, its development trend, comparisons with previous years.